Hubungan Safety Leadership terhadap Safety Behavior Pekerja Metal Working PT Inka (Persero) - Hanifah, Sholikhatul Yus (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Safety behavior or safe behavior is an action taken by humans in order to avoid or prevent unwanted events or work accidents. Employee safety behavior is a reflection of the existence of leadership in an organization. Safety leadership is a process of interaction between leaders and subordinates, where the role of the leader as a superior is able to influence subordinates to achieve occupational safety and health goals. Safety leadership has three main dimensions namely, safety motivation, safety policy, and safety concern. This study was conducted to analyze the relationship between safety leadership and worker safety behavior. This study is an observational descriptive  research conducted at PT INKA (Persero) using a cross-sectional  research design.The respondents in this study were calculated using the Slovin formula and obtained as many as 85 respondents. The data of this study was analyzed with the help of SPSS (Statistical Package for the Social Sciences) software  with the Chi Square test. The results show that safety motivation (p=0.000), safety concern (p=0.033), and safety policy (p=0.000) have a significant influence on the dependent safety behavior variables. The conclusion in this study is that safety leadership has a significant relationship with  the safety of metal working workers  at PT INKA (Persero). Keywords: Safety Behavior, Safety Policy, Safety Motivation, Safety Concern  ABSTRAK Safety behavior atau perilaku selamat merupakan suatu tindakan yang dilakukan oleh manusia dalam rangka menghindari atau mencegah peristiwa yang tidak diinginkan atau kecelakaan kerja. Safety behavior pekerja merupakan cerminan dari adanya leadership atau kepemimpinan dalam suatu organisasi. Safety leadership atau kepemimpinan keselamatan merupakan proses interaksi antara pemimpin dan bawahan, di mana peran pemimpin sebagai atasan yang mampu mempengaruhi bawahan untuk tercapainya tujuan keselamatan dan kesehatan kerja. safety leadership mempunyai tiga dimensi utama yaitu, safety motivation, safety policy, dan safety concern. Penelitian ini dilakukan untuk menganalisis hubungan safety leadership terhadap safety behavior pekerja. Penelitian ini merupakan penelitian deskriptif observational yang dilakukan di PT INKA (Persero) dengan menggunakan desain penelitian cross-sectional. Responden dalam penelitian ini dihitung menggunakan rumus Slovin dan diperoleh sebanyak 85 responden. Data penelitian ini di analisis bantuan software SPSS (Statistical Package for the Social Sciences) dengan uji Chi Square. Hasil penelitian menunjukkan bahwa safety motivation (p=0,000), safety concern (p=0,033), dan safety policy (p=0,000) memiliki pengaruh yang signifikan terhadap variabel dependen safety behavior. Kesimpulan dalam penelitian ini yaitu, safety leadership memiliki hubungan yangsignifikan terhadap safety behavor pekerja metal working di PT INKA (Persero). Kata Kunci: Safety Behavior, Safety Policy, Safety Motivation, Safety Concern